2011
DOI: 10.3390/ijms12095592
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate (EGCG) for Clinical Trials: More Pitfalls than Promises?

Abstract: Epigallocatechin-3-gallate (EGCG), the main and most significant polyphenol in green tea, has shown numerous health promoting effects acting through different pathways, as antioxidant, anti-inflammatory and anti-atherogenic agent, showing gene expression activity, functioning through growth factor-mediated pathways, the mitogen-activated protein kinase-dependent pathway, the ubiquitin/proteasome degradation pathway, as well as eliciting an amyloid protein remodeling activity. However, epidemiological inference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
224
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(227 citation statements)
references
References 45 publications
1
224
0
2
Order By: Relevance
“…Plasma concentrations close to 1 μM were achieved in mice after oral administration of EGCG (75 mg/kg) [105]. Oral administration of EGCG (450 mg) or green tea extract (1.2-4.5 g, corresponding to 100-300 mg EGCG) resulted in similar peak plasma concentrations in humans [106][107][108]. While EGCG has been recognized to be hepatotoxic in mice at concentrations of 500 mg/kg body weight and above and sporadic incidents of hepatotoxicity in humans have been reported [109,110], daily doses of 800 mg EGCG have been used in clinical trials without adverse effects (clinical trial NCT00951834) [111].…”
Section: Perspectives For Prevention and Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma concentrations close to 1 μM were achieved in mice after oral administration of EGCG (75 mg/kg) [105]. Oral administration of EGCG (450 mg) or green tea extract (1.2-4.5 g, corresponding to 100-300 mg EGCG) resulted in similar peak plasma concentrations in humans [106][107][108]. While EGCG has been recognized to be hepatotoxic in mice at concentrations of 500 mg/kg body weight and above and sporadic incidents of hepatotoxicity in humans have been reported [109,110], daily doses of 800 mg EGCG have been used in clinical trials without adverse effects (clinical trial NCT00951834) [111].…”
Section: Perspectives For Prevention and Therapymentioning
confidence: 99%
“…However, a widely recognized problem in the therapeutic application of EGCG is the large variability in the bioavailability of orally administered EGCG (reviewed in [108] and [112]). This is owing to its high sensitivity to oxidation, the tendency to conjugate to proteins in the digestive tract (e.g., casein), and rapid metabolism in the body.…”
Section: Perspectives For Prevention and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In another study green tea extract administration was found to be effective in enhancing learning and memory in aged rats, and also demonstrated selectivity for inhibition of AChE [82]. In recent years, green tea has been explored in clinical trials relating to learning and memory-related disorders, indicating its potential for improving learning and memory [83]. In a randomized, double-blind, placebo-controlled study, a combination of green tea extract and L-theanine (LGNC-07) showed potential cognitive improvement in patients with MCI [84].…”
Section: Green Teamentioning
confidence: 99%
“…Methylation decreases the hydrophilicity of catecholic compounds; further sulfation/glucuronidation of the methylated product is usually needed for the elimination of the product from the body. 11,12 There has been discussion that level of methylation is influenced by polymorphisms of catechol-Omethyltransferase, but the effect of this has not yet been fully studied. Within the plasma, serum albumin contributes to transport and stabilization by directly preventing EGCG oxidation.…”
Section: Introductionmentioning
confidence: 99%